THE EXTENT OF USING MODERN TECHNOLOGY IN TEACHING METHODS - Wadiyan Hassan Ali (PT. Antis International Publisher, 2026)
Objective: This research highlights the impact of integrating modern technology, specifically Artificial Intelligence (AI) and interactive learning tools, into teaching methods, and their direct role in elevating the quality of higher education. The research problem stems from the continued reliance on classical methods and theoretical indoctrination, which creates a comprehension gap and diminishes student motivation, in addition to addressing the challenges of teaching staff shortages. The research aims to emphasize the inevitability of transitioning towards interactive learning environments based on the